Enhancing Oral Academic English as a Medium of Instruction (EMI) through self-regulated Listening to Authentic Educational Podcast - Wubalem, Abebe Yitbarek (Colombian Applied Linguistics Journal, 2022)
This study investigated the role of self-regulated listening practice to authentic lecture podcast in improving oral English for instructional purposes. It employed an experimental study design complemented by qualitative tools. The participants (56 teachers) were drawn from a population of upper secondary school subject area teachers. The data was generated through classroom observation scheme and in-depth interview. Independent sample t-test and thematic analysis were employed to analyze the quantitative data (from the observation) and qualitative data (from the interview) respectively. The results showed that a combined use of listening to authentic lecture podcast and self-regulated listening strategies play an important role in improving English language deficiency of teachers for instructional purposes across discourse functions of lesson introduction, definition, elaboration, hypothesizing and use of discourse markers. The discourse functions of questioning remain largely unaffected. The positive results have promising educational implications suggesting the possibility of using this package of intervention in pre-service and in-service teacher training programs to enhance EMI teachers’ oral English for instructional ends.